Fungal-derived extracts induce resistance against Botrytis cinerea in Arabidopsis thaliana - Hael Conrad, Veronica; Tomas-Grau, Rodrigo H.; Moschen, Sebastian Nicolas; Requena-Serra, F.J.; Díaz Ricci, Juan Carlos; Salazar, Sergio Miguel (Springer, 2020)
Development of a sustainable agriculture is a current trend searching for alternative and more environmentally friendly strategies to control crop diseases. The necrotrophic fungus Botrytis cinerea, the causal agent of grey mould, affects crops pre- and post-harvest and cause huge economical losses. Microorganisms and microbially-derived elicitors are known to induce plant defences. Here, we study two fungal extracts derived from Colletotrichum acutatum (isolate M11). The crude extract, called CF (culture filtrate) and the semi-purified fraction ACF (axenic culture filtrate) consist in a blend of fungal-derived elicitors. Their activities were evaluated in the plant-pathogen system Arabidopsis thaliana-B. cinerea. Both CF and ACF induced local and systemic resistance, rendering A. thaliana resistant against grey mould disease. The extracts showed no antifungal activity since no inhibition of mycelium growth, changes in hyphal ultrastructure or damage in cell membrane permeability were observed. These findings would indicate that the protective effect was indirect and it was found that CF and ACF induced up-regulation of the defence-related genes PR1, WRKY70 and ERF6, as well as giving local callose deposition in treated leaves. Both fungal extracts have the potential to be used as a main component of a biologically based disease control product with activity against grey mould, with the advantage that the purification process of CF is simpler than for ACF.